Let's solve the equation step by step. The equation you provided is:
\[ \frac{2}{3}x - 5 = 27 \]
Step 1:
Add 5 to both sides of the equation to isolate the term with \(x\):
\[ \frac{2}{3}x - 5 + 5 = 27 + 5 \] Which simplifies to:
\[ \frac{2}{3}x = 32 \]
Step 2:
Multiply both sides by \(\frac{3}{2}\) to solve for \(x\):
\[ x = 32 \cdot \frac{3}{2} \] Calculating that gives:
\[ x = 48 \]
Solution:
The solution to the equation is \(x = 48\).
So, fill in the responses:
Step 1: Add 5 to both sides.
Step 2: Multiply both sides by \(\frac{3}{2}\).
Solution: \(x = 48\).